(untitled) (Journal of Information Technologies in Education (ITE), 2013)
In the article it is considered the actuality of creation of virtual educational communities,which form innovative educational environments in the systems of education of foreign countries and in Ukraine; determined the criteria for their forming; descriptions of virtual educational environments as well as the importance of their forming in general educational establishments are given. There are presented some examples of the most popular virtual educational communities.